Comparative evaluation of nasopharyngeal swab and saliva specimens for the molecular detection of SARS-CoV-2 RNA in Japanese patients with COVID-19. Issue 1 (January 2021) - Sakanashi, Daisuke; Asai, Nobuhiro; Nakamura, Akiko; Miyazaki, Narimi; Kawamoto, Yuzuka; Ohno, Tomoko; Yamada, Atsuko; Koita, Isao; Suematsu, Hiroyuki; Hagihara, Mao; Shiota, Arufumi; Kurumiya, Ai; et al.
Abstract: Considering the issues of shortage of medical resources and the invasiveness and infection risk involved in the collection of nasopharyngeal swab specimens, there is a need for an effective alternative test specimen for SARS-CoV-2 RNA detection. Here, we investigated suitability of saliva as a non-invasively obtained specimen for molecular detection of SARS-CoV-2 RNA in Japanese patients with COVID-19. In total, 28 paired clinical specimens of saliva and nasopharyngeal swabs were collected from 12 patients at various time points after symptom onset. Each specimen was assayed using reverse transcription real-time polymerase chain reaction (rRT-PCR) on the BD MAX open system using primers and probes targeting the N-gene. The saliva and nasopharyngeal swab specimens showed 19 and 15 positive results, respectively. No invalid (PCR inhibition) result was observed for any specimen. The qualitative results of each specimen obtained in the period immediately after symptom onset were similar. Three convalescent patients presented saliva-positive results, whereas their nasopharyngeal swabs were negative at four different time points, suggesting that saliva may be superior to nasopharyngeal swabs in terms of obtaining stable assay result of SARS-CoV-2. In conclusion, our results suggest that saliva can potentially serve as an alternative to nasopharyngeal swabs as a specimen for SARS-CoV-2 rRT-PCR. As saliva can be collected by patients themselves, it may be an effective way to overcome the shortage of personal protective equipment and specimen sampling tools.